In Limbo: Time Perspective and Memory Deficit Among Female Survivors of Sexual Abuse - Jacobs-Kayam, Angi; Lev-Wiesel, Rachel (Frontiers in Psychology, 2019)
Child sexual abuse (CSA) is a worldwide phenomenon with negative outcomes for survivors whose lives and well-being are compromised into adulthood, due to the trauma caused by the abuse. As trauma survivors often report time and space disorientation as well as memory deficit, an attempt was made to further understand these functions in female adults CSA survivors. More specifically, we questioned how they recalled their past; how their past experience interacted with their experience of the present; and how the past abuse affected the way that they viewed the future. A total of 50 adult female CSA survivors’ open-ended life story interviews were analyzed utilizing Thematic Content Analysis. In relation to time perception and memory deficit, three main themes emerged: Adrift in time and space; disintegration of body, mind and identity; and chaos, exhaustion, and confusion. These themes were discussed from the conceptual perspective of “captured in a distorted time,” which is one of the traumagenic constructs of childhood sexual abuse.